A solvent-free composite polypropylene matte film with controllable gloss and preparation method thereof

Through the preparation method of solvent-free composite polypropylene matte film, the use of composite light control agents to achieve precise control of gloss, solving the problems of insufficient gloss control and environmental pollution in traditional polypropylene films, and improving the visual and tactile effects of the product. And reduce production costs.

CN119101474BActive Publication Date: 2025-02-25DEZHOU QUNLI PLASTIC CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411575787.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-25
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

Traditional polypropylene films have shortcomings in gloss control, which cannot effectively enhance product texture and visual effects, and the use of organic solvents during the compounding process leads to environmental pollution.

Method used

The preparation method of solvent-free composite polypropylene matte film is adopted, and the matte layer, support layer, connection layer and adhesive layer are sequentially superimposed and coextruded, and the composite light control agent is used to achieve precise control of gloss.

Benefits of technology

It achieves precise control of gloss, improves the visual and tactile effects of the product, avoids environmental pollution caused by the use of organic solvents, reduces production costs and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119101474B_ABST
    Figure CN119101474B_ABST
Patent Text Reader

Abstract

The invention relates to the field of polypropylene films, and in particular to a solvent-free composite polypropylene matte film with controllable gloss and a preparation method thereof, which are used to solve the problems that the existing polypropylene films have limited light control properties, are difficult to accurately control the gloss, are easy to pollute the environment, and are difficult to meet the needs of different application scenarios; the main raw material of the solvent-free composite polypropylene matte film is a matte masterbatch, and a composite light control agent is added to the matte masterbatch, which can achieve accurate control of the gloss, thereby meeting the needs of different application occasions for the gloss of the film, enabling the film to obtain the best visual and tactile effects in different applications, and providing diversified choices for various industries, thereby improving its market competitiveness; and no organic solvent is needed during use, which not only reduces production costs and improves production efficiency, but also significantly reduces environmental pollution, is conducive to green and sustainable development, and achieves multiple goals of environmental protection, energy saving, and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polypropylene films, and in particular to a solvent-free composite polypropylene matte film with controllable glossiness and a preparation method thereof. Background Art

[0002] As an important thermoplastic, polypropylene is widely used in packaging, construction, automobiles and other fields due to its good physical properties, chemical stability and processing performance. However, traditional polypropylene films have deficiencies in gloss control and cannot effectively enhance product texture and visual effects. They have poor scattering rate and anti-glare properties and are difficult to meet the needs of high-end applications with more stringent gloss requirements. In addition, organic solvents are used in the compounding process, resulting in the generation of a large amount of volatile organic compounds, which pollute the environment.

[0003] Therefore, it is of great practical significance to develop a gloss-controllable, solvent-free, gloss-controllable solvent-free composite polypropylene matte film and a preparation method thereof. Summary of the invention

[0004] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide a solvent-free composite polypropylene matte film with controllable gloss and a preparation method thereof, which solves the problems that the existing polypropylene film has limited light control properties, the gloss is difficult to accurately control, and it is easy to pollute the environment and difficult to meet the needs of different application scenarios.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A solvent-free composite polypropylene matte film with controllable glossiness, which is formed by sequentially stacking and co-extruding a matte layer, a support layer, a connecting layer and an adhesive layer;

[0007] The matte layer comprises the following components in mass ratio: 95-98% matte masterbatch and 2-5% anti-blocking agent; wherein the matte masterbatch comprises the following components in weight: 45-75 parts of binary copolymer polypropylene resin, 20-40 parts of high-density polyethylene, 5-15 parts of linear low-density polyethylene, 5-9 parts of composite light control agent and 0.1-0.5 parts of antioxidant 1010; wherein the anti-blocking agent is one of silicon dioxide, calcium carbonate, calcined silica, kaolin and polymethyl methacrylate;

[0008] The support layer comprises the following components in mass ratio: homopolymer polypropylene 97-99%, antistatic masterbatch 1-3%;

[0009] The connecting layer is one or more of linear low-density polyethylene, high-pressure polyethylene, ethylene-vinyl acetate copolymer and maleic anhydride grafted product;

[0010] The adhesive layer is one or more of ethylene-vinyl acetate copolymer, ethylene-α-olefin copolymer and maleic anhydride grafted modified ethylene-α-olefin copolymer.

[0011] As a further solution of the present invention: the composite light control agent is prepared by the following steps:

[0012] Step a1: 2,4-dihydroxybenzophenone, glycidyl methacrylate and chloroform are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 25-30° C. and a stirring rate of 300-400 r / min for 20-30 min, and then Amberlyst-15 ion exchange resin is added to continue stirring for reaction for 5-10 min. The mixture is then heated to 60-65° C. and stirred for reaction for 3-5 h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain an intermediate product;

[0013] Step a2: adding the intermediate product, γ-methacryloxypropyltrimethoxysilane, azobisisobutyronitrile, anhydrous toluene and anhydrous ethanol to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introducing nitrogen protection, stirring the reaction at a temperature of 25-30° C. and a stirring rate of 300-400 r / min for 20-30 min, then heating to 60-65° C. and continuing to stir the reaction for 3-5 h. After the reaction is completed, the reaction product is cooled to room temperature, then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain a polymer modifier;

[0014] Step a3: titanium dioxide and deionized water are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, nitrogen is introduced for protection, ultrasonic dispersion is performed for 30-40 minutes under an ultrasonic power of 300-350W, sodium hexafluorophosphate is added, and the reaction is stirred for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, and then the temperature is raised to 80-85°C and water glass is added dropwise while stirring, and the dropping rate is controlled to be 1-2 drops / s. After the dropwise addition is completed, the pH is adjusted to 9-10 with sulfuric acid solution, and then the stirring reaction is continued for 1-2 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then aged for 2-3 hours, and then centrifuged. The precipitate is washed with anhydrous methanol 2-3 times, and then placed in a vacuum drying oven, and dried at a temperature of 60-65°C for 2-3 hours to obtain silicon-coated titanium dioxide;

[0015] Step a4: Add silicon-coated titanium dioxide and deionized water to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, introduce nitrogen protection, ultrasonically disperse for 30-40 minutes under an ultrasonic power of 300-350W, then add sodium hexafluorophosphate and stir the reaction for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat to 60-65°C and add sodium aluminate solution dropwise while stirring, control the dropping rate to 1-2 drops / s, adjust the pH to 9-10 with sulfuric acid solution after the dropwise addition is completed, and then continue to stir the reaction for 1-2 hours. After the reaction is completed, cool the reaction product to room temperature, then stand and age for 2-3 hours, then centrifuge, wash the precipitate with anhydrous methanol 2-3 times, then place it in a vacuum drying oven, and dry it at a temperature of 60-65°C for 2-3 hours to obtain aluminum-silicon-coated titanium dioxide;

[0016] Step a5: Add aluminum silicon coated titanium dioxide, anhydrous ethanol and deionized water to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir the reaction for 40-50 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then add a polymer modifier and continue stirring the reaction for 3-5 hours at a temperature of 80-85°C. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed with anhydrous methanol for 2-3 times, and then placed in a vacuum drying oven and dried at a temperature of 60-65°C for 2-3 hours to obtain a composite light control agent.

[0017] As a further solution of the present invention: the thickness of the matte layer is 1.0-2.0 μm, the thickness of the support layer is 10-15 μm, the thickness of the connecting layer is 1.0-3.0 μm, and the thickness of the adhesive layer is 2.0-6.0 μm.

[0018] As a further solution of the present invention: the usage ratio of the 2,4-dihydroxybenzophenone, glycidyl methacrylate, chloroform and Amberlyst-15 ion exchange resin in step a1 is 10 mmol: 10 mmol: 10-15 mL: 0.2-0.4 g.

[0019] As a further solution of the present invention: the usage ratio of the intermediate product in step a2, γ-methacryloxypropyltrimethoxysilane, azobisisobutyronitrile, anhydrous toluene and anhydrous ethanol is 10 mmol: 10 mmol: 0.005-0.01 g: 20-25 mL: 20-25 mL.

[0020] As a further solution of the present invention: the usage ratio of the titanium dioxide, deionized water, sodium hexafluorophosphate and water glass in step a3 is 10g:45-55mL:0.04-0.08g:30-35mL.

[0021] As a further solution of the present invention: the molar concentration of the water glass in step a3 is 0.3-0.5 mol / L; the mass fraction of the sulfuric acid solution is 5-10%.

[0022] As a further solution of the present invention: the usage ratio of the silicon-coated titanium dioxide, deionized water, sodium hexafluorophosphate and sodium aluminate solution in step a4 is 10 g: 45-55 mL: 0.04-0.08 g: 30-35 mL.

[0023] As a further solution of the present invention: the molar concentration of the sodium aluminate solution in step a4 is 0.6-0.8 mol / L; the mass fraction of the sulfuric acid solution is 5-10%.

[0024] As a further solution of the present invention: the dosage ratio of the aluminum silicon-coated titanium dioxide, anhydrous ethanol, deionized water and polymer modifier in step a5 is 5g:50-60mL:10-15mL:0.8-2.4g.

[0025] As a further solution of the present invention: a method for preparing a solvent-free composite polypropylene matte film with controllable glossiness comprises the following steps:

[0026] Step S1: the raw materials of the matte layer, the support layer, the connecting layer and the adhesive layer are mixed evenly according to proportions, and are respectively put into different extruders for melting and plasticization; wherein the temperature of the extruder for the matte layer raw material is 220-240°C, the temperature of the extruder for the support layer raw material is 230-250°C, and the temperature of the extruder for the connecting layer and the adhesive layer raw material is 200-250°C;

[0027] Step S2: filtering the melt of the matte layer through a 250-mesh filter, filtering the melt of the support layer, the connecting layer and the adhesive layer through a 320-mesh filter respectively, and then sequentially extrude the melts of each layer in a die head with a four-layer structure to obtain a melt co-extruded thick sheet;

[0028] Step S3: placing the melt-coextruded thick sheet close to a rotating cold roller under the action of an air knife to complete the sheet casting process, and removing water through a water bath and air knife to obtain a membrane;

[0029] Step S4: subjecting the film to a longitudinal stretching process to obtain a longitudinally stretched film;

[0030] Step S5: subjecting the longitudinally stretched film to a transverse stretching process to obtain a longitudinally and transversely stretched film;

[0031] Step S6: cooling the longitudinally and transversely stretched film, cutting off the thick edge, and then corona treating and rolling up to obtain a large roll film;

[0032] Step S7: subjecting the large roll film to aging treatment, slitting and packaging to obtain a solvent-free composite polypropylene matte film with controllable glossiness.

[0033] As a further solution of the present invention: the casting temperature during the casting process in step S3 is 20-45°C.

[0034] As a further solution of the present invention: the longitudinal stretching temperature in the longitudinal stretching process in step S4 is 95-138° C., and the longitudinal stretching ratio is 4.5-5.8.

[0035] As a further solution of the present invention: the transverse stretching temperature in the transverse stretching process in step S5 is 150-170° C., and the transverse stretching ratio is 8-10 times.

[0036] As a further solution of the present invention: the corona treatment power of the corona treatment in step S6 is 18-35Wmin / m 2 .

[0037] Beneficial effects of the present invention:

[0038] The present invention discloses a solvent-free composite polypropylene matte film with controllable gloss and a preparation method thereof. The main raw material of the solvent-free composite polypropylene matte film is a matte masterbatch, and a composite light control agent is added to the matte masterbatch, which can realize accurate control of gloss, thereby meeting the requirements of different application occasions for film gloss, so that the film can obtain the best visual and tactile effects in different applications, and can provide diversified choices for various industries, thereby improving its market competitiveness. In addition, no organic solvent is required during use, which not only reduces production costs and improves production efficiency, but also significantly reduces environmental pollution, is conducive to green and sustainable development, and achieves multiple goals of environmental protection, energy saving, and economic benefits.

[0039] In the process of preparing a solvent-free composite polypropylene matte film with controllable gloss, a composite light control agent is first prepared. First, 2,4-dihydroxybenzophenone and glycidyl methacrylate are reacted, a hydroxyl group on 2,4-dihydroxybenzophenone reacts with an epoxy group on glycidyl methacrylate, an alkenyl group is introduced, and an intermediate product is obtained. Then, the intermediate product and γ-methacryloxypropyltrimethoxysilane are reacted, and the alkenyl group on the intermediate product reacts with the alkenyl group on γ-methacryloxypropyltrimethoxysilane to obtain a polymer modifier containing a large number of benzophenone structures and siloxane groups. Then, silicon dioxide is coated on the surface of titanium dioxide after water glass hydrolysis to obtain silicon-coated titanium dioxide. Then, aluminum oxide is coated on the surface of silicon-coated titanium dioxide after sodium aluminate solution to obtain aluminum-silicon-coated titanium dioxide. Finally, aluminum-silicon-coated titanium dioxide and the polymer modifier are reacted to obtain a high molecular weight modifier. The siloxane on the molecular modifier is hydrolyzed to form silanol, which is then grafted onto the surface of aluminum-silicon-coated titanium dioxide particles to obtain a composite light control agent. The core of the composite light control agent is titanium dioxide, which has an excellent matting effect. After being coated with aluminum silicon, its wear resistance and scratch resistance can be effectively improved, while the photocatalytic performance of titanium dioxide can be inhibited to avoid the photocatalytic effects on the mechanical properties, visual effects and aesthetics of the film. After being modified with a polymer modifier, the dispersibility of titanium dioxide can be greatly improved, so that it can be evenly distributed in the film, and the gloss of the film is uniform. The large amount of grafted benzophenone structures have excellent ultraviolet light absorption properties, which not only improves the matting effect of titanium dioxide, but also avoids aging of the film under light and high temperature environments, thereby improving the optical properties of the film, further realizing the precise control of the gloss and transparency of the film, and maintaining stable performance even after long-term exposure to harsh environments, thereby extending the service life of the film. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The present invention will be further described below in conjunction with the accompanying drawings.

[0041] Figure 1 The schematic diagram is a structural diagram of a solvent-free composite polypropylene matte film with controllable glossiness in the present invention. DETAILED DESCRIPTION

[0042] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Example 1: Please refer to Figure 1As shown, this embodiment is a solvent-free composite polypropylene matte film with controllable glossiness, which is formed by sequentially stacking and co-extruded matte layer, support layer, connecting layer and adhesive layer;

[0044] The matte layer comprises the following components in mass ratio: 97% matte masterbatch and 3% anti-blocking agent; wherein the matte masterbatch comprises the following components in weight: 45 parts of binary copolymer polypropylene resin, 20 parts of high-density polyethylene, 5 parts of linear low-density polyethylene, 5 parts of composite light control agent and 0.1 parts of antioxidant 1010; wherein the binary copolymer polypropylene resin is Lanzhou Petrochemical T10F; the anti-blocking agent is silicon dioxide;

[0045] The support layer comprises the following components in mass ratio: homopolymer polypropylene 98.5% and antistatic masterbatch 1.5%; wherein the homopolymer polypropylene is HB28F from North China Petrochemical; and the antistatic masterbatch is Constant AT4030;

[0046] The connecting layer is linear low-density polyethylene;

[0047] The adhesive layer is 670 from DuPont of the United States;

[0048] The method for preparing the solvent-free composite polypropylene matte film with controllable glossiness comprises the following steps:

[0049] Step Q1: 10 mmol 2,4-dihydroxybenzophenone, 10 mmol glycidyl methacrylate and 10 mL chloroform were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred for reaction at 25° C. and a stirring rate of 300 r / min for 20 min, and then 0.2 g Amberlyst-15 ion exchange resin was added and the mixture was stirred for reaction for 5 min. The mixture was heated to 60° C. and stirred for reaction for 3 h. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered. The filtrate was rotary evaporated to remove the solvent to obtain an intermediate product.

[0050] Step Q2: 10 mmol of the intermediate product, 10 mmol of γ-methacryloxypropyltrimethoxysilane, 0.005 g of azobisisobutyronitrile, 20 mL of anhydrous toluene and 20 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then the temperature was raised to 60° C. and the stirring reaction was continued for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, and the filtrate was rotary evaporated to remove the solvent to obtain a polymer modifier;

[0051] Step Q3: 10g of titanium dioxide and 45mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen was introduced for protection. Ultrasonic dispersion was performed for 30min under the condition of ultrasonic power of 300W, and then 0.04g of sodium hexafluorophosphate was added and stirred for 20min at a temperature of 25°C and a stirring rate of 300r / min. Then, 30mL of water glass with a molar concentration of 0.3mol / L was added dropwise while stirring at 80°C, and the dropping rate was controlled to be 1 drop / s. After the dropwise addition was completed, the pH was adjusted to 9 with a sulfuric acid solution with a mass fraction of 5%, and then the stirring reaction was continued for 1h. After the reaction was completed, the reaction product was cooled to room temperature, and then aged for 2h, and then centrifuged. The precipitate was washed twice with anhydrous methanol, and then placed in a vacuum drying oven and dried at a temperature of 60°C for 2h to obtain silicon-coated titanium dioxide;

[0052] Step Q4: 10 g of silicon-coated titanium dioxide and 45 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen was introduced for protection. Ultrasonic dispersion was performed for 30 min under an ultrasonic power of 300 W, and then 0.04 g of sodium hexafluorophosphate was added and stirred for 20 min at a temperature of 25 ° C and a stirring rate of 300 r / min. Then, 30 mL of a sodium aluminate solution with a molar concentration of 0.6 mol / L was added dropwise while stirring at 60 ° C. The dropping rate was controlled to be 1 drop / s. After the dropwise addition was completed, the pH was adjusted to 9 with a mass fraction of 5% sulfuric acid solution, and then the stirring reaction was continued for 1 h. After the reaction was completed, the reaction product was cooled to room temperature, and then aged for 2 h, and then centrifuged. The precipitate was washed twice with anhydrous methanol, and then placed in a vacuum drying oven and dried at a temperature of 60 ° C for 2 h to obtain aluminum-silicon-coated titanium dioxide;

[0053] Step Q5: 5 g of aluminum-silicon-coated titanium dioxide, 50 mL of anhydrous ethanol and 10 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The mixture was stirred for 40 min at a temperature of 25° C. and a stirring rate of 300 r / min. Then, 0.8 g of a polymer modifier was added and the mixture was heated to 80° C. and the stirring reaction was continued for 3 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed twice with anhydrous methanol and then placed in a vacuum drying oven and dried at 60° C. for 2 h to obtain a composite light control agent.

[0054] Step Q6: The raw materials of the matte layer, the support layer, the connecting layer and the adhesive layer are mixed evenly according to a certain proportion, and are respectively put into different extruders for melting and plasticization; wherein the temperature of the extruder for the matte layer raw material is 220° C., the temperature of the extruder for the support layer raw material is 230° C., and the temperature of the extruder for the connecting layer and the adhesive layer raw material is 200° C.;

[0055] Step Q7: filtering the melt of the matte layer through a 250-mesh filter, filtering the melts of the support layer, the connecting layer and the adhesive layer through a 320-mesh filter respectively, and then sequentially extrude the melts of each layer in a die head with a four-layer structure to obtain a melt co-extruded thick sheet;

[0056] Step Q8: The molten co-extruded thick sheet is placed on a rotating cold roller under the action of an air knife to complete the casting process. The casting temperature is 20°C. The film is removed by water bath and air knife to obtain a membrane.

[0057] Step Q9: subjecting the film to a longitudinal stretching process, wherein the longitudinal stretching temperature is 95° C. and the longitudinal stretching ratio is 4.7, to obtain a longitudinally stretched film;

[0058] Step Q10: subjecting the longitudinally stretched film to a transverse stretching process, wherein the transverse stretching temperature is 150° C. and the transverse stretching ratio is 9 times, to obtain a longitudinally and transversely stretched film;

[0059] Step Q11: Cool the longitudinally and transversely stretched film, cut off the thick edge, then corona treat and roll it up to obtain a large roll film; the corona treatment power is 18Wmin / m 2 ;

[0060] Step Q12: The large roll film is subjected to aging treatment, slitting and packaging to obtain a solvent-free composite polypropylene matte film with controllable glossiness.

[0061] Example 2: Please refer to Figure 1 As shown, this embodiment is a solvent-free composite polypropylene matte film with controllable glossiness, which is formed by sequentially stacking and co-extruded matte layer, support layer, connecting layer and adhesive layer;

[0062] The matte layer comprises the following components in mass ratio: 97% matte masterbatch and 3% anti-blocking agent; wherein the matte masterbatch comprises the following components in weight: 60 parts of binary copolymer polypropylene resin, 30 parts of high-density polyethylene, 10 parts of linear low-density polyethylene, 7 parts of composite light control agent and 0.3 parts of antioxidant 1010; wherein the binary copolymer polypropylene resin is Lanzhou Petrochemical T10F; the anti-blocking agent is calcium carbonate;

[0063] The support layer comprises the following components in mass ratio: homopolymer polypropylene 98.5% and antistatic masterbatch 1.5%; wherein the homopolymer polypropylene is HB28F from North China Petrochemical; and the antistatic masterbatch is AS2335PP from Best;

[0064] The connecting layer is high-pressure polyethylene;

[0065] The adhesive layer is a mixture of EF320 from LG Chemical of South Korea and LF100 from LG Chemical in a mass ratio of 4:6;

[0066] The method for preparing the solvent-free composite polypropylene matte film with controllable glossiness comprises the following steps:

[0067] Step Q1: 10 mmol 2,4-dihydroxybenzophenone, 10 mmol glycidyl methacrylate and 13 mL chloroform were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then 0.3 g Amberlyst-15 ion exchange resin was added and the stirring reaction was continued for 8 min. The mixture was then heated to 62° C. and the stirring reaction was continued for 4 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filtrate was rotary evaporated to remove the solvent to obtain an intermediate product;

[0068] Step Q2: 10 mmol of the intermediate product, 10 mmol of γ-methacryloxypropyltrimethoxysilane, 0.008 g of azobisisobutyronitrile, 22 mL of anhydrous toluene and 22 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred at 28° C. and a stirring rate of 350 r / min for 25 min, and then the mixture was heated to 62° C. and stirred for 4 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filtrate was rotary evaporated to remove the solvent to obtain a polymer modifier;

[0069] Step Q3: 10 g of titanium dioxide and 50 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen was introduced for protection. Ultrasonic dispersion was performed for 35 min under an ultrasonic power of 325 W, and then 0.06 g of sodium hexafluorophosphate was added and stirred for 25 min at a temperature of 28° C. and a stirring rate of 350 r / min. Then, 32 mL of water glass with a molar concentration of 0.4 mol / L was added dropwise while stirring at 82° C. The dropping rate was controlled to be 1 drop / s. After the dropwise addition was completed, the pH was adjusted to 9.5 with a sulfuric acid solution with a mass fraction of 8%, and then the stirring reaction was continued for 1.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then aged for 2.5 h, and then centrifuged. The precipitate was washed twice with anhydrous methanol, and then placed in a vacuum drying oven and dried at a temperature of 62° C. for 2.5 h to obtain silicon-coated titanium dioxide;

[0070] Step Q4: 10 g of silicon-coated titanium dioxide and 50 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen was introduced for protection. Ultrasonic dispersion was performed for 35 min under an ultrasonic power of 325 W, and then 0.06 g of sodium hexafluorophosphate was added and stirred for 25 min at a temperature of 28° C. and a stirring rate of 350 r / min. Then, 32 mL of a sodium aluminate solution with a molar concentration of 0.7 mol / L was added dropwise while stirring at 62° C. The dropping rate was controlled to be 1 drop / s. After the dropwise addition was completed, the pH was adjusted to 9.5 with a 7% sulfuric acid solution, and then the stirring reaction was continued for 1.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then aged for 2.5 h, and then centrifuged. The precipitate was washed twice with anhydrous methanol, and then placed in a vacuum drying oven and dried at a temperature of 62° C. for 2.5 h to obtain aluminum-silicon-coated titanium dioxide;

[0071] Step Q5: 5 g of aluminum-silicon-coated titanium dioxide, 55 mL of anhydrous ethanol and 12 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The mixture was stirred at 28° C. and a stirring rate of 350 r / min for 45 min. Then, 1.6 g of a polymer modifier was added and the mixture was heated to 82° C. and the stirring reaction was continued for 4 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed twice with anhydrous methanol and then placed in a vacuum drying oven and dried at 62° C. for 2.5 h to obtain a composite light control agent.

[0072] Step Q6: The raw materials of the matte layer, the support layer, the connecting layer and the adhesive layer are mixed evenly according to a certain proportion, and are respectively put into different extruders for melting and plasticization; wherein the temperature of the extruder for the matte layer raw material is 230°C, the temperature of the extruder for the support layer raw material is 240°C, and the temperature of the extruder for the connecting layer and the adhesive layer raw material is 225°C;

[0073] Step Q7: filtering the melt of the matte layer through a 250-mesh filter, filtering the melts of the support layer, the connecting layer and the adhesive layer through a 320-mesh filter respectively, and then sequentially extrude the melts of each layer in a die head with a four-layer structure to obtain a melt co-extruded thick sheet;

[0074] Step Q8: The melt co-extruded thick sheet is placed on a rotating cold roller under the action of an air knife to complete the casting process. The casting temperature is 32°C. The film is removed by water bath and air knife to obtain a membrane.

[0075] Step Q9: subjecting the film to a longitudinal stretching process, wherein the longitudinal stretching temperature is 116° C. and the longitudinal stretching ratio is 4.7, to obtain a longitudinally stretched film;

[0076] Step Q10: subjecting the longitudinally stretched film to a transverse stretching process, wherein the transverse stretching temperature is 160° C. and the transverse stretching ratio is 9 times, to obtain a longitudinally and transversely stretched film;

[0077] Step Q11: Cool the longitudinally and transversely stretched film, cut off the thick edge, then corona treat and roll it up to obtain a large roll film; the corona treatment power is 27Wmin / m 2 ;

[0078] Step Q12: The large roll film is subjected to aging treatment, slitting and packaging to obtain a solvent-free composite polypropylene matte film with controllable glossiness.

[0079] Example 3: Please refer to Figure 1 As shown, this embodiment is a solvent-free composite polypropylene matte film with controllable glossiness, which is formed by sequentially stacking and co-extruded matte layer, support layer, connecting layer and adhesive layer;

[0080] The matte layer comprises the following components in mass ratio: 97% matte masterbatch and 3% anti-blocking agent; wherein the matte masterbatch comprises the following components in weight: 75 parts of binary copolymer polypropylene resin, 40 parts of high-density polyethylene, 15 parts of linear low-density polyethylene, 9 parts of composite light control agent and 0.5 parts of antioxidant 1010; wherein the binary copolymer polypropylene resin is Lanzhou Petrochemical T10F; the anti-blocking agent is kaolin;

[0081] The support layer comprises the following components in mass ratio: homopolymer polypropylene 98.5% and antistatic masterbatch 1.5%; wherein the homopolymer polypropylene is Lanzhou Petrochemical T28FE; the antistatic masterbatch is Constant AT4030;

[0082] The connecting layer is ethylene-vinyl acetate copolymer;

[0083] The adhesive layer is EXACT POE 9061 ethylene-butene copolymer from ExxonMobil of the United States;

[0084] The method for preparing the solvent-free composite polypropylene matte film with controllable glossiness comprises the following steps:

[0085] Step Q1: 10 mmol 2,4-dihydroxybenzophenone, 10 mmol glycidyl methacrylate and 15 mL chloroform were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then 0.4 g Amberlyst-15 ion exchange resin was added and the stirring reaction was continued for 10 min. Then, the temperature was raised to 65° C. and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, and the filtrate was rotary evaporated to remove the solvent to obtain an intermediate product;

[0086] Step Q2: 10 mmol of the intermediate product, 10 mmol of γ-methacryloxypropyltrimethoxysilane, 0.01 g of azobisisobutyronitrile, 25 mL of anhydrous toluene and 25 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the temperature was raised to 65° C. and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, and the filtrate was rotary evaporated to remove the solvent to obtain a polymer modifier;

[0087] Step Q3: 10 g of titanium dioxide and 55 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen was introduced for protection. Ultrasonic dispersion was performed for 40 min under an ultrasonic power of 350 W, and then 0.08 g of sodium hexafluorophosphate was added and stirred for 30 min at a temperature of 30° C. and a stirring rate of 400 r / min. Then, 35 mL of water glass with a molar concentration of 0.5 mol / L was added dropwise while stirring at 85° C., and the dropping rate was controlled to 2 drops / s. After the dropwise addition was completed, the pH was adjusted to 10 with a 10% sulfuric acid solution, and then the stirring reaction was continued for 2 h. After the reaction was completed, the reaction product was cooled to room temperature, and then aged for 3 h, and then centrifuged. The precipitate was washed 3 times with anhydrous methanol, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 3 h to obtain silicon-coated titanium dioxide;

[0088] Step Q4: 10 g of silicon-coated titanium dioxide and 55 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen was introduced for protection. Ultrasonic dispersion was performed for 40 min under an ultrasonic power of 350 W, and then 0.08 g of sodium hexafluorophosphate was added and stirred for 30 min at a temperature of 30° C. and a stirring rate of 400 r / min. Then, 35 mL of a sodium aluminate solution with a molar concentration of 0.8 mol / L was added dropwise while stirring at 65° C., and the dropping rate was controlled to be 2 drops / s. After the dropwise addition was completed, the pH was adjusted to 10 with a 10% sulfuric acid solution, and then the stirring reaction was continued for 2 h. After the reaction was completed, the reaction product was cooled to room temperature, and then aged for 3 h, and then centrifuged. The precipitate was washed 3 times with anhydrous methanol, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 3 h to obtain aluminum-silicon-coated titanium dioxide;

[0089] Step Q5: 5 g of aluminum-silicon-coated titanium dioxide, 60 mL of anhydrous ethanol and 15 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 50 min. Then, 2.4 g of a polymer modifier was added and the mixture was heated to 85° C. and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed 3 times with anhydrous methanol and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 3 h to obtain a composite light control agent.

[0090] Step Q6: The raw materials of the matte layer, the support layer, the connecting layer and the adhesive layer are mixed evenly according to a certain proportion, and are respectively put into different extruders for melting and plasticization; wherein the temperature of the extruder for the matte layer raw material is 240°C, the temperature of the extruder for the support layer raw material is 250°C, and the temperature of the extruder for the connecting layer and the adhesive layer raw material is 250°C;

[0091] Step Q7: filtering the melt of the matte layer through a 250-mesh filter, filtering the melts of the support layer, the connecting layer and the adhesive layer through a 320-mesh filter respectively, and then sequentially extrude the melts of each layer in a die head with a four-layer structure to obtain a melt co-extruded thick sheet;

[0092] Step Q8: The melt co-extruded thick sheet is placed on a rotating cold roller under the action of an air knife to complete the casting process. The casting temperature is 45°C. The film is removed by water bath and air knife to obtain a membrane.

[0093] Step Q9: subjecting the film to a longitudinal stretching process, wherein the longitudinal stretching temperature is 138° C. and the longitudinal stretching ratio is 4.7, to obtain a longitudinally stretched film;

[0094] Step Q10: subjecting the longitudinally stretched film to a transverse stretching process, wherein the transverse stretching temperature is 170° C. and the transverse stretching ratio is 9 times, to obtain a longitudinally and transversely stretched film;

[0095] Step Q11: Cool the longitudinally and transversely stretched film, cut off the thick edge, then corona treat and roll it up to obtain a large roll film; the corona treatment power is 35Wmin / m 2 ;

[0096] Step Q12: The large roll film is subjected to aging treatment, slitting and packaging to obtain a solvent-free composite polypropylene matte film with controllable glossiness.

[0097] Comparative Example 1:

[0098] The difference between this comparative example and Example 3 is that the matte layer comprises the following components in mass ratio: 97% of matte masterbatch and 3% of anti-blocking agent; wherein the matte masterbatch comprises the following components in weight parts: 75 parts of binary copolymer polypropylene resin, 40 parts of high-density polyethylene, 15 parts of linear low-density polyethylene, 9 parts of calcium carbonate and 0.5 parts of antioxidant 1010; wherein the binary copolymer polypropylene resin is Lanzhou Petrochemical T10F; and the anti-blocking agent is kaolin.

[0099] Comparative Example 2:

[0100] The difference between this comparative example and Example 3 is that the matt layer comprises the following components in mass ratio: 97% matt masterbatch and 3% anti-blocking agent; wherein the matt masterbatch comprises the following components in weight parts: 75 parts of binary copolymer polypropylene resin, 40 parts of high-density polyethylene, 15 parts of linear low-density polyethylene, 9 parts of titanium dioxide and 0.5 parts of antioxidant 1010; wherein the binary copolymer polypropylene resin is Lanzhou Petrochemical T10F; and the anti-blocking agent is kaolin.

[0101] Comparative Example 3:

[0102] The difference between this comparative example and Example 3 is that the matte layer comprises the following components in mass ratio: 97% matte masterbatch and 3% anti-blocking agent; wherein the matte masterbatch comprises the following components in weight parts: 75 parts of binary copolymer polypropylene resin, 40 parts of high-density polyethylene, 15 parts of linear low-density polyethylene, 9 parts of 2,4-dihydroxybenzophenone and 0.5 parts of antioxidant 1010; wherein the binary copolymer polypropylene resin is Lanzhou Petrochemical T10F; and the anti-blocking agent is kaolin.

[0103] The performance of the solvent-free composite polypropylene matte film with controllable gloss in Examples 1-3 and Comparative Examples 1-3 was tested according to GB / T 2410-2008 "Determination of light transmittance and haze of transparent plastics", and the thickness of the matte layer in the solvent-free composite polypropylene matte film with controllable gloss was controlled to be 1.5±0.1 μm, the thickness of the support layer was 13.0±0.1 μm, the thickness of the connecting layer was 2.0±0.1 μm, and the thickness of the adhesive layer was 4.0±0.1 μm. The test results are as follows:

[0104] .

[0105] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-3, it can be known that the addition of the composite light control agent has greatly improved the gloss and haze performance of the gloss-controllable solvent-free composite polypropylene matte film.

[0106] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0107] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A solvent-free composite polypropylene matte film with controllable gloss, characterized in that: It is formed by sequentially stacking and co-extruding a matte layer, a supporting layer, a connecting layer and an adhesive layer; The matte layer comprises the following components in mass ratio: 95-98% matte masterbatch and 2-5% anti-blocking agent; wherein the matte masterbatch comprises the following components in weight: 45-75 parts of binary copolymer polypropylene resin, 20-40 parts of high-density polyethylene, 5-15 parts of linear low-density polyethylene, 5-9 parts of composite light control agent and 0.1-0.5 parts of antioxidant 1010; The support layer comprises the following components in mass ratio: homopolymer polypropylene 97-99%, antistatic masterbatch 1-3%; The connecting layer is one or more of linear low-density polyethylene, high-pressure polyethylene, ethylene-vinyl acetate copolymer and maleic anhydride grafted product; The adhesive layer is one or more of ethylene-vinyl acetate copolymer, ethylene-α-olefin copolymer and maleic anhydride grafted modified ethylene-α-olefin copolymer; Wherein, the composite light control agent is prepared by the following steps: Step a1: 2,4-dihydroxybenzophenone, glycidyl methacrylate and chloroform are stirred for reaction, and then Amberlyst-15 ion exchange resin is added and the reaction is continued with stirring. After the reaction is completed, the reaction product is cooled, and then vacuum filtered, and the filtrate is rotary evaporated to obtain an intermediate product; Step a2: stirring the intermediate product, γ-methacryloxypropyltrimethoxysilane, azobisisobutyronitrile, anhydrous toluene and anhydrous ethanol for reaction, cooling the reaction product after the reaction is completed, and then vacuum filtering, and rotary evaporating the filtrate to obtain a polymer modifier; Step a3: ultrasonically disperse titanium dioxide and deionized water, then add sodium hexafluorophosphate to react with stirring, then add water glass dropwise while stirring, adjust the pH with sulfuric acid solution after the addition is complete, then continue stirring the reaction, and after the reaction is completed, cool the reaction product, then stand for aging, then centrifuge, wash and dry the precipitate to obtain silicon-coated titanium dioxide; Step a4: ultrasonically disperse silicon-coated titanium dioxide and deionized water, then add sodium hexafluorophosphate for stirring reaction, then add sodium aluminate solution dropwise while stirring, adjust the pH with sulfuric acid solution after the addition is complete, then continue stirring the reaction, and after the reaction is completed, cool the reaction product, then stand for aging, then centrifuge, wash and dry the precipitate to obtain aluminum-silicon-coated titanium dioxide; Step a5: Stir and react aluminum silicon-coated titanium dioxide, anhydrous ethanol and deionized water, then add a polymer modifier and continue stirring the reaction. After the reaction is completed, cool the reaction product, then centrifuge it, wash and dry the precipitate to obtain a composite light control agent.

2. The solvent-free composite polypropylene matte film with controllable glossiness according to claim 1, characterized in that: The thickness of the matte layer is 1.0-2.0 μm, the thickness of the support layer is 10-15 μm, the thickness of the connecting layer is 1.0-3.0 μm, and the thickness of the adhesive layer is 2.0-6.0 μm.

3. The solvent-free composite polypropylene matte film with controllable glossiness according to claim 1, characterized in that: The usage ratio of the 2,4-dihydroxybenzophenone, glycidyl methacrylate, chloroform and Amberlyst-15 ion exchange resin in step a1 is 10 mmol: 10 mmol: 10-15 mL: 0.2-0.4 g.

4. The solvent-free composite polypropylene matte film with controllable glossiness according to claim 1, characterized in that: The usage ratio of the intermediate product, γ-methacryloxypropyltrimethoxysilane, azobisisobutyronitrile, anhydrous toluene and anhydrous ethanol in step a2 is 10 mmol: 10 mmol: 0.005-0.01 g: 20-25 mL: 20-25 mL.

5. The solvent-free composite polypropylene matte film with controllable glossiness according to claim 1, characterized in that: The dosage ratio of the titanium dioxide, deionized water, sodium hexafluorophosphate and water glass in step a3 is 10g:45-55mL:0.04-0.08g:30-35mL; the molar concentration of the water glass is 0.3-0.5mol / L; and the mass fraction of the sulfuric acid solution is 5-10%.

6. The solvent-free composite polypropylene matte film with controllable glossiness according to claim 1, characterized in that: The dosage ratio of the silicon-coated titanium dioxide, deionized water, sodium hexafluorophosphate and sodium aluminate solution in step a4 is 10g:45-55mL:0.04-0.08g:30-35mL; the molar concentration of the sodium aluminate solution is 0.6-0.8mol / L; and the mass fraction of the sulfuric acid solution is 5-10%.

7. The solvent-free composite polypropylene matte film with controllable glossiness according to claim 1, characterized in that: The dosage ratio of the aluminum silicon-coated titanium dioxide, anhydrous ethanol, deionized water and polymer modifier in step a5 is 5g: 50-60mL: 10-15mL: 0.8-2.4g.

8. A method for preparing a solvent-free composite polypropylene matte film with controllable glossiness according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step S1: the raw materials of the matte layer, the support layer, the connecting layer and the adhesive layer are mixed evenly according to proportions, and are respectively put into different extruders for melting and plasticization; wherein the temperature of the extruder for the matte layer raw material is 220-240°C, the temperature of the extruder for the support layer raw material is 230-250°C, and the temperature of the extruder for the connecting layer and the adhesive layer raw material is 200-250°C; Step S2: filtering the melt of the matte layer through a 250-mesh filter, filtering the melt of the support layer, the connecting layer and the adhesive layer through a 320-mesh filter respectively, and then sequentially extrude the melts of each layer in a die head with a four-layer structure to obtain a melt co-extruded thick sheet; Step S3: placing the melt-coextruded thick sheet close to a rotating cold roller under the action of an air knife to complete the sheet casting process, and removing water through a water bath and air knife to obtain a membrane; Step S4: subjecting the film to a longitudinal stretching process to obtain a longitudinally stretched film; Step S5: subjecting the longitudinally stretched film to a transverse stretching process to obtain a longitudinally and transversely stretched film; Step S6: cooling the longitudinally and transversely stretched film, cutting off the thick edge, and then corona treating and rolling up to obtain a large roll film; Step S7: subjecting the large roll film to aging treatment, slitting and packaging to obtain a solvent-free composite polypropylene matte film with controllable glossiness.

9. The method for preparing a solvent-free composite polypropylene matte film with controllable glossiness according to claim 8, characterized in that: The casting temperature in the casting process in step S3 is 20-45°C; the longitudinal stretching temperature in the longitudinal stretching process in step S4 is 95-138°C, and the longitudinal stretching ratio is 4.5-5.8; the transverse stretching temperature in the transverse stretching process in step S5 is 150-170°C, and the transverse stretching ratio is 8-10 times; the corona treatment power in step S6 is 18-35Wmin / m 2 .

Citation Information

Patent Citations

  • Matte BOPP film and preparation method thereof

    CN105128472A

  • Gradient-color antistatic PET film and preparation method thereof

    CN113308201A